Objective Surveys for Dynamic Forestry and Forest Industries Development in India - Mahalaha, S. H. (Indian Forester, 1968)
In this paper, an attempt has been made to introduce a concept of dynamic forestry management for the development of forestry and industries based on forest raw materials. The wood based industries desire to have conventional raw material of their choice at rates calculated by them, providing very low royalty and from the areas most convenient for logging, whereas the forest departments want to give only silviculturally available scattered material with due regard to soil and water conservation at the current market rates, thereby creating a static deadlock in both forestry and forest industries development. A dynamic balance based on comprehensive studies of all factors involved is needed to break this deadlock. The necessity of an integrated approach which involves parallel and synchronised investigations of all closely inter-related factors of supply, demand and costs have been stressed. The need for enunciating clear end-objectives in forestry surveys for proper implementation has been detailed and the need for the preparation of produce oriented industrial management plans as against conventional area oriented plans has been emphasized. In the end, the need for a specialised agency for conducting integrated and continuous surveys to plan for and watch the progress of forestry and forest industries development suggested.